Anemoside B4 Protects Rat Kidney from Adenine-Induced Injury by Attenuating Inflammation and Fibrosis and Enhancing Podocin and Nephrin Expression. (2nd May 2019) - Gong, Qin; He, Lu-Ling; Wang, Mu-Lan; Ouyang, Hui; Gao, Hong-Wei; Feng, Yu-Lin; Yang, Shi-Lin; Du, Li-Jun; Li, Jun; Luo, Ying-Ying
Abstract : Anemoside B4 (B4) isolated from Radix Pulsatilla has anti-inflammatory activities in the colon and antitumor effects. However, its role in the prevention and treatment of kidney injury has not been reported. Here, we reported the effects of B4 on chronic kidney injury (CKI) and studied its related mechanism based on an adenine-induced kidney injury model in rats. The results showed that serum BUN (blood urea nitrogen), Crea (creatinine), and urinary proteins increased significantly after oral administration of adenine. Meanwhile, the adenine contents in both renal tissue and urine increased markedly compared with those of normal rats. Moreover, IL-1 β, IL-6, TNF α, and NF κ B expression was upregulated in the kidney. Simultaneously, the expression of NLRP3 (the nucleotide-binding and oligomerization domain–like receptor, leucine-rich repeat and pyrin domain–containing 3) in the inflammasome, which consists of Caspase 1, ASC (apoptosis-associated speck - like protein containing a caspase recruitment domain), and IL-18, was significantly upregulated. B4 could significantly decrease BUN and Crea; reduce urinary proteins in rats; suppress the expression of IL-6, IL-1 β, NF κ B, NLRP3, Caspase 1, ASC, and IL-18; and increase urinary adenine contents and promote its excretion. In addition, B4 also upregulated the expression of podocin and nephrin, two major podocyte proteins, and reduced the fiber collagen in the renal interstitial, suggesting that B4 could protect the glomerular matrix from adenine injury in addition to its anti-inflammatory effects. The results of this study show new perspective of B4 as a potential drug against adenine-induced renal injury.